Application of Response Surface Methodology in the Formulation of Sustained Release Matrix Tablets of Metformin Hydrochloride - Ghosh, A.; Bose, A.; Bhaumik, U.; Mandal, U.; Veeran Gowda, K.; Pal, T.K. (Asian Journal of Chemistry, 2010)
The aim of the current research was to design an oral sustained release (SR) matrix tablet of metformin HCl (400 mg) and to optimize the drug release profile by using response surface methodology (RSM). Tablets were prepared by non-aqueous wet granulation method using hydroxy propyl methyl cellulose (HPMC K-15 M) and sodium carboxy methyl cellulose (Na CMC) as matrix forming polymers. Independent variables such as HPMC K-15 M (X1), Na CMC (X2) and polyvinyl pyrrolidone (PVP K-30) (X3) were optimized by using a 3-factor, 3-level Box-Behnken statistical design. The dependent variables selected were cumulative percentage of drug release after 1 h (Y1), 2 h (Y2), 4 h (Y3), 6 h (Y4), 8 h (Y5) and 10 h (Y6). The values of Y1, Y2, Y3, Y4, Y5 and Y6 were restricted to not more than 30, 40, 60, 70, 90 and 110 %, respectively. It was found that both of the polymers and binder had significant effects on the drug release from the tablets (p < 0.05). The formulated tablets followed the Higuchi drug release kinetics and the diffusion was the dominant mechanism of drug release, resulting in regulated and complete release within 10 h. For estimation of coefficients in the approximating polynomial function, the least square regression method was applied. Afterward, the information about the model reliability was verified by using the analysis of variance (ANOVA). The result showed that the optimized formulation provided a dissolution pattern equivalent to the predicted values (residual values varies from -2.4271 to 2.1348), which indicated that the optimal formulation could be obtained by using response surface methodology.